PROGRAMMATIC DIAGNOSIS OF DIGESTIVE SYSTEM DISORDERS IN CATTLE BASED ON CLINICAL AND LABORATORY PARAMETERS (EVIDENCE FROM 100 CASES) - Faxriddinovna, Fayziyeva Sitora; Baratovna, Mamatova Zamira; Fayzullayevna, Normurodova Zuhra; Baxtiyorovna, Gulliyeva Sabina (Research Focus International Scientific Journal, 2026)
This article describes the methods of software-based diagnostics of digestive system diseases in cattle based on clinical and laboratory parameters. The research was conducted on 100 dairy cows in livestock farms of the Samarkand region. The study utilized the vet- diagnostics.uz digital platform to perform a complex analysis of clinical signs, hematological, and biochemical blood parameters. The results indicated that the digital diagnostic system provides higher accuracy (92–95%) and rapid processing (2–5 minutes) compared to traditional methods. The effectiveness of the software algorithm was particularly proven in detecting the subclinical stages of diseases. The article substantiates the importance of integrating a veterinarian’s professional expertise with digital technologies to increase livestock productivity and economic efficiency.